Filamentous Phytophthora Pathogens Deploy Effectors to Interfere With Bacterial Growth and Motility - Wang, Ji; Shen, Danyu; Ge, Chengcheng; Du, Yaxin; Lin, Long; Liu, Jin; Bai, Tian; Jing, Maofeng; Qian, Guoliang; Dou, Daolong (Frontiers in Microbiology, 2020)
Phytophthora comprises a group of filamentous plant pathogens that cause serious crop diseases worldwide. It is widely known that a complex effector repertoire was secreted by Phytophthora pathogens to manipulate plant immunity and determine resistance and susceptibility. It is also recognized that Phytophthora pathogens may habit in natural niches within complex environmental microbes, including bacteria. However, how Phytophthora pathogens interact with their co-habited microbes remains poorly understood. Here, we present such an intriguing case by using Phytophthora-bacteria interaction as a working system. We found that under co-culture laboratory conditions, several Phytophthora pathogens appeared to block the contact of an ecologically-relevant bacterium, including Pseudomonas fluorescence and a model bacterium, Escherichia coli. We further observed P. sojae utilizes a conserved Crinkler (CRN) effector protein, PsCRN63, to impair bacterial growth. P. capsici deploys another CRN effector, PcCRN173 to interfere with bacterial flagellum- and/or type IV pilus-mediated motility whereas a P. capsici-derived RxLR effector, PcAvh540, inhibits bacterial swimming motility, but not twitching motility and biofilm formation, suggesting of functional diversification of effector-mediated Phytophthora-bacteria interactions. Thus, our studies provide a first case showing the filamentous Phytophthora pathogens could deploy effectors to interfere bacterial growth and motility, revealing an unprecedented effector-mediated inter-kingdom interaction between Phytophthora pathogens and bacterial species, and thereby uncovering ecological significance of effector proteins in filamentous plant pathogens besides their canonical roles involving in pathogen-plant interaction.